FRANCOIST REPRESSION AND MORAL REPARATION IN THE THEATRE OF LAILA RIPOLL - García-Pascual, Raquel (Signa: Revista de la Asociación Española de Semiótica, 2018)
This article focuses on a corpus of dramatic texts by Laila Ripoll that denounce how the Spanish Civil War, the Francoist dictatorship and Republican exile marked the lives of the people involved, those of their children and those of generations to come. The author highlights the collective responsibility of the creative community to reveal details left out from the past by an authoritarian regime and specifically emphasises that this ethical stance is linked to the outlook of their generation, that of the grandchildren of war. The works chosen demonstrate that members of this third generation of victims are attempting to incorporate the events experienced by their ancestors into the public memory, supported by in-depth research work. The article also argues that to do this, Ripoll makes use of the critical power of the grotesque aesthetic, a longstanding tradition on the Spanish stage.